Student problem set with solutions [for] Electric circuit analysis - Conahan, Steven G. (Prentice Hall, 1996)
Introduction. Resistive circuits. Dependent sources and op amps. Analysis methods. Energy storage elements. First-order circuits. Sinusoidal sources and phasors. AC steady state analysis. AC steady state power. Three-phase circuits. Laplace transform. Circuit analysis in the s-domain. Frequency response. mutual inductance and transformers...